Redox-Related Epigenetic Mechanisms in Glioblastoma: Nuclear Factor (Erythroid-Derived 2)-Like 2, Cobalamin, and Dopamine Receptor Subtype 4 - Schrier, Matthew Scott; Trivedi, Malav Suchin; Deth, Richard Carlton (Frontiers in Oncology, 2017)
Glioblastoma is an exceptionally difficult cancer to treat. Cancer is universally marked by epigenetic changes, which play key roles in sustaining a malignant phenotype, in addition to disease progression and patient survival. Studies have shown strong links between the cellular redox state and epigenetics. Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a redox-sensitive transcription factor that upregulates endogenous antioxidant production, and is aberrantly expressed in many cancers, including glioblastoma. Methylation of DNA and histones provides a mode of epigenetic regulation, and cobalamin-dependent reactions link the redox state to methylation. Antagonists of dopamine receptor subtype 4 (D4 receptor) were recently shown to restrict glioblastoma stem cell growth by downregulating trophic signaling, resulting in inhibition of functional autophagy. In addition to stimulating glioblastoma stem cell growth, D4 receptors have the unique ability to catalyze cobalamin-dependent phospholipid methylation. Therefore, D4 receptors represent an important node in a molecular reflex pathway involving Nrf2 and cobalamin, operating in conjunction with redox status and methyl group donor availability. In this article, we describe the redox-related effects of Nrf2, cobalamin metabolism, and the D4 receptor on the regulation of the epigenetic state in glioblastoma.